Pola Komunikasi dalam IPNU Kota Surabaya 2014-2016 dalam Membangun Jaringan - Azam, Mochamad; Syueb, Sudono (Jurnal Komunikasi Profesional, 2017)
This Research Entitled "Communication Pattern Organization Branch Manager Association Student Nahdhatul Ulama (PC IPNU) Surabaya City Khitmat Period 2014-2016 In Building Communication Network Organization". The purpose of this research is to know the communication pattern run by IPNU organization in IPNU PC communication relationship with Banom NU, leadership structure with organization member, and top management of IPNU Regional Leadership. data techniques that researchers use in this study are literature study and field observation field study (field obersvasi) and in-depth interview (in-depth interview). Based on the results of the research, showed the Head of IPNU Branch of Surabaya as an organization of learning and is one of the autonomous bodies of the big umbrella of Nahdlatul Ulama Branch Head of Surabaya City building communication pattern of internal organization organization and between organization is downward communication pattern, upward communication, horizontal communication This pattern is reinforced by the role of the core daily management in the internal realm of the organization, and the Head of Surabaya IPNU Branch as the center of communicationKeywords: Organizational Communication Patterns, downward communication, upward communication, horizontal communicationÂ Â Â